PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PEMALSUAN MATERAI OLEH PENGADILAN NEGERI PEKANBARU - Prayudi, Arga; Jayakusuma, Zulfikar; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Stamp duty has an important meaning in society, that is with stamp duty, the stamped letter specified by the Act becomes a valid letter, meaning that without stamp duty as a certificate, for example a power of attorney, it is unaccepted as a valid authorization. Likewise in court proceedings, new letters can be used as a means of proof if stamped with those determined by the law. Stamp counterfeiting is detrimental to the government because stamp purchases are a kind of tax and stamp forgery results in a reduction in the state taxex.This research is a sociological legal research that is research that wants to see the unity between law and society with the gap between das sollen and das sein. This research was conducted at the Pekanbaru District Court, while the population and sample were all parties related to the issues examined in this study, the data sources used, primary data, and secondary data, the data collection techniques in this study were conducted through literature review interviews.in this thesis, three things that can be concluded. First, the application of sanctions against stamped offenders by the Pekanbaru District Court. Second, the factors which become obstacles faced in the application of criminal sanctions by the perpetrators of falsified criminal acts. Third, the efforts made in overcoming obstacles to the imposition of criminal sanctions against perpetrators of stamp fraud by the Pekanbaru District Court.Keywords: Application of Sanctions - Stamp Counterfeiting Criminal Acts